A study on prevalence and pattern of clinically recognisable congenital malformations in babies born in a rural medical college hospital in West Bengal, India - Dr. Subhendu Dey; Dr. Abhay Charan Pal; Dr. Malay Kumar Nandi; Dr. Prasant Agarwalla (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Congenital anomalies are a major cause of neonatal mortality and morbidity both in developed and developing countries. It accounts for 8-15% of perinatal deaths and 13-16% of neonatal deaths in India.Aims and Objective: This study was done to determine the proportion and changing pattern of congenital anomalies in live newborns and to study the associated maternal and perinatal risk factors.Materials and Method: This is a hospital based cross-sectional descriptive study and was conducted in Bankura Sammalini Medical College and Hospital, West Bengal India during the period July 2016 to December 2017.Results: During his period 31989 babies were born, of which 598 had congenital malformations, making the prevalence 1.86%. Distribution of malformation was predominant among males than in females (66.7 vs. 32.6%; p < 0.05).Discussion: The predominant system involved was musculo-skeletal system followed by cardiovascular and genitourinary system. Congenital anomalies were more likely associated with low birth weight, prematurity, multiparity, consanguinity and caesarean delivery. Various maternal risk factors were studied as well as the role of early preventive interventionalstrategies.Conclusion: Public awareness is to be created and early prenatal diagnosis and management of common anomalies is highly recommended.